An osteobiography of a Oaxacan late adolescent female. (June 2017) - Alfaro Castro, Martha Elena; Waters-Rist, Andrea L.; Zborover, Danny
Abstract: Skeleton Sk-CV-1 is the first and only human skeleton known from controlled excavations in the Chontal region of Oaxaca in southern Mexico. This approximately 17-year-old female was carefully buried in a stone cist between the 14th and 16th century CE, a time period of great transformations for which there are only a few analyzed skeletons in the State of Oaxaca. The archaeological context and historical documentation associate her with the Chontal people who still inhabit the region, and whose contemporary practices serve as ethnographic analogies for this study. In this article we present the archaeological, osteological, and stable isotope analyses of this unique skeleton, to give a first glimpse into the diseases, activities, and diet of this little known ethnic group and time period. Highlights: First and only archaeological human skeleton from Chontal region of Oaxaca Bioarchaeological research on diet, disease and activity of 17 ± 2 year-old female Importance of maize clear in stable isotope, pathology, and activity results Multiple pathological lesions reveal malnutrition and probable infectious disease Building block upon which a regional database can be built